Repair revolution how fixers are transforming our throwaway culture - Wackman, John; Knight, Elizabeth (New World Library, 2020)
"Repair Revolution chronicles the rise of repair cafés: non-profit, volunteer organizations devoted to repairing electronics and household items for free. After outlining the philosophy of repair cafés, the book discusses practical details such as online repair resources, fixes for common product malfunctions, and tips for founding new repair cafés
Includes bibliographical references (pages (257-287) and index